Automatic Clothes Folder With Three Folding Modes Based on Microcontroller - Desi; Ella Andini Br Ginting; Mutiara Damarani; Ratna Anzani; Sumarlin; Ita Margaretta Br Tarigan (Karya Techno Solusindo, 2025)
In the digital era and increasingly rapid automation, technological innovation continues to penetrate various aspects of life, including household work. One household task that is often considered boring and time-consuming is folding clothes. Even though it looks simple, this activity can be a burden, especially in the context of modern society, where time is limited. The main feature of this system is its ability to fold clothes with three different folding modes. This provides the flexibility to handle different types of clothing or different fold preferences. The folding mechanism is implemented using a Tower Pro MG995 servo motor, which is programmed to move precisely using the Servo library. The design of an automatic system for folding clothes in three different modes is to build a tool that will use the Arduino Uno R3 microcontroller as a control center that coordinates all system operations. Next, the folding mechanism is implemented using a Tower Pro MG 995 servo motor, which is programmed to move precisely using a servo library. REFERENCES Ahmad, S. R., & Faikul, U. (2021). Project sistem kontrol berbasis Arduino. Tim MNC Publishing.Alifiah, U., Buatin, R., & Lumbanbatu, K. (2023). Rancang bangun lengan robot mikrokontroler dengankendali smartphone berbasis Internet of Things. Jurnal, 1(3).Churniawan, M. B., Sani, M. I., & Meisaroh, L. (2023). Rancang bangun alat pelipat pakaian otomatismenggunakan sensor ultrasonik berbasis mikrokontroler Arduino Uno.Fathulrohman, Y. N. I., Saepuloh, A., & Kom, M. (2018). Alat monitoring suhu dan kelembabanmenggunakan Arduino Uno. Jurnal, 2(1).Gunawan, I. K. W., Nurkholis, A., Sucipto, A., & Afifudin, A. (2020). Sistem monitoring kelembabangabah padi berbasis Arduino. JTIKOM, 1(1), 1–7. https://doi.org/10.33365/jtikom.v1i1.Hariyanti, E., Tambunan, G., Saputra, R. A., Basjaruddin, N. C., & Rakhman, E. (2020). Alat pelipatpakaian otomatis dengan tiga mode pelipatan berbasis mikrokontroler.Kusumah, H., Mukhtar, H., & Sari, D. P. (2021). Implementation of Arduino-based smart home system.International Journal of Electrical and Computer Engineering, 11(3), 2088–8708.Lubis, A. I., Saniman, S., & Yetri, M. (2022). Sistem kendali lampu ruangan menggunakan metode fuzzy logic dan Android berbasis mikrokontroler. JURSIK TGD, 1(1), 1–9.https://doi.org/10.53513/jursik.v1i1.4800Mattalatta, A. H., Hanafie, A., Suradi, & Baco, S. (2023). Rancangan alat pelipat sarung otomatis berbasis mikrokontroler dalam penerapan ergonomis. JRI, 5(1), 10–18. https://doi.org/10.37631/jri.v5i1.852Meliana, Y., & Hwihanus, H. (2022). Analisis peranan dan kegunaan sistem informasi akuntansi pada PT Kurnia Eka Nusa yang berbasis Accurate-Desktop. Inisiatif, 2(1), 362–374. https://doi.org/10.30640/inisiatif.v2i1.537Nugraha, A., & Sari, L. (2021). Pengembangan antarmuka pengguna menggunakan teknologi LCD pada sistem kendali rumah pintar. Jurnal Teknologi Informasi dan Ilmu Komputer, 8(2), 167–176.Nugroho, A., & Setiawan, B. (2024). Analisis dan desain sistem informasi terintegrasi untuk optimalisasirantai pasok. Jurnal Manajemen Teknologi, 18(2), 112–128.Nurdin, N., Chechen, A. R., & Fatmawati, I. (n.d.). Robot pembantu pembibitan rumput laut berbasismikrokontroler.Pratama, R. A., Ardiyanto, A., & Suryanegara, M. (2020). Design of IoT-based heart rate monitoringsystem using Arduino. Journal of Electrical and Electronic Engineering, 8(1), 1–6.Putra, R., & Sari, M. (2021). Pengembangan sistem alarm kebakaran menggunakan sensor asap dan buzzer.Jurnal Teknologi Informasi dan Ilmu Komputer, 9(1), 78–86.Rahardjo, P. (2021). Sistem penyiraman otomatis menggunakan RTC (Real Time Clock) berbasismikrokontroler Arduino Mega 2560 pada tanaman mangga harum manis Buleleng Bali. Spektrum, 8(1),143. https://doi.org/10.24843/SPEKTRUM.2021.v08.i01.p16Rahmawati, A., Prasetyo, D., & Nugroho, E. (2020). Implementasi buzzer pada sistem peringatan dinibanjir berbasis IoT. Jurnal Teknik Elektro, 14(3), 125–132.Rismawati, R., Paembonan, S., & Suppa, R. (2024). Rancang bangun keamanan pintu otomatismenggunakan e-KTP berbasis Arduino Uno. JITET, 12(3). https://doi.org/10.23960/jitet.v12i3.4745 Saptono, M. P., & Sumbiaganan, A. (2020). LPG gas leakage prototype based on ATmega328 and LCDmicrocontroller as information media. JELEKN, 6(1), 82–92. https://doi.org/10.32531/jelekn.v6i1.200Surya, C., & Azizah, J. (2021). Sistem informasi akuntansi laporan laba rugi pada PNPM Mandiri Kelurahan Air Jamban. Jurnal, 2.Tambunan, I. T., Handoko, S., Sari, N. G., Pribadi, A., & Rangkuty, D. M. (2023). Studi kajian strategi promosi bisnis pakaian berbasis offline dan online. JREA-ITB, 1(2), 158–166. https://doi.org/10.54066/jrea-itb.v1i2.280Tambunan, S., & Stefanie, A. (2023). Monitoring kebocoran gas LPG menggunakan sensor MQ-2 pada rumah dengan notifikasi bot Telegram. JATI, 7(2), 1423–1228. https://doi.org/10.36040/jati.v7i2.6815Wandana, N. P. (2023). Menggunakan sensor hujan dengan motor DC berbasis Arduino Nano.